Use of silver nanoparticles to suppress Cucumber mosaic virus (CMV) in ginger (Zingiber officinale Roscoe) and turmeric (Curcuma longa L.) - Vadamalai, Ganesan; Muhammad, Buhari; Kong, Lih Ling; Lau, Wei Hong (Taylor & Francis, 2024)
Plant viruses have remained a nuisance to profitable and sustainable crop cultivation; and concerted efforts have been exercised to salvage this menace. In this study, the efficacy of silver nanoparticles (AgNPs) against Cucumber mosaic virus (CMV) in ginger and turmeric plants was investigated using the technique of quantitative real-time PCR (qRT-PCR) using SYBR Green. The plants comprising three groups; treated, untreated and healthy controls were mechanically inoculated with a purified CMV suspension at early plant growth. The virus concentration was then measured after the inoculation before silver nanoparticles were applied at 20 ppm per treated plant. The virus concentration significantly declined after the suppressive effect by AgNPs (p < 0.01) in the treated plants from one-month post-inoculation (MPI) and sustained through 5 MPI. Thus, AgNPs have provided an avenue for the management of CMV infection in ginger and turmeric.